Avian Pasteurella multocida induces chicken macrophage apoptosis by inhibiting the Zyxin-FAK-AKT-FoxO1/NF-κB axis - Pan Li; Guangfu Zhao; Tao Tang; Fang He; Xiongli Liu; Nengzhang Li; Yuanyi Peng (Poultry Science)
Pasteurella multocida (P. multocida) can cause infection in various animals, especially livestock and poultry, which can lead to substantial losses to the breeding industry. However, the pathogenesis of avian P. multocida remains largely unknown. In this study, the mechanisms of avian P. multocida pathogenesis were explored. Chicken macrophage HD11 cells were infected with the avian strain PmQ and the bovine strain PmCQ2. PmQ induced higher cytotoxicity and apoptosis and exerted a stronger anti-phagocytotic effect on HD11 cells than PmCQ2. RNA sequencing analysis revealed that focal adhesion (FA)-related genes were significantly downregulated in PmQ-infected HD11 cells compared with that of PmCQ2. Subsequently, phalloidin staining of the F-actin assembly revealed that PmQ more significantly inhibited the formation of FAs in HD11 than PmCQ2. Western blot analysis revealed that the levels of Zyxin and phosphorylated focal adhesion kinase (FAK) were significantly decreased in PmQ-infected cells, confirming that PmQ inhibited FAs. Consequently, PmQ inhibited the FA downstream factor Akt, which decreased NF-κB and FoxO1 phosphorylation, as evidenced by the decreased expression of downstream anti-apoptotic genes (GADD45B, BCL2L1, BCL2A1, and BIRC2) and increased expression of downstream pro-apoptotic genes (BCL6, PKL2, PKL3, and KLF2). Conversely, pharmaceutically inhibiting FA formation using latrunculin A better enhanced PmCQ2-induced than PmQ-induced apoptosis in HD11 cells. Similarly, the knockdown of Zyxin or FoxO1 by siRNA both boosted the PmCQ2-induced apoptosis rates equal to those of PmQ. These results demonstrated that PmQ inhibited Zyxin-dependent FA formation and disrupted the FAK-AKT-FoxO1/NF-κB pathway to induce apoptosis in chicken macrophages. This study thus offers insights into the pathogenesis of avian P. multocida, which could facilitate the development of new strategies against P. multocida infection.